EFFECT OF DIETARY INCLUSION OF DRIED MUSHROOM (Pleurotus ostreatus) ON THE BLOOD PARAMETERS AND LIPID PROFILES OF BROILER CHICKENS AT STARTER PHASE - S. N, Okey; C.L, Iwuji (Kashere Journal of Animal Science, 2025)
60 day old broiler chicks of either sex were randomly distributed into four treatments groups (T1, T2, T3 and T4) with each treatment having three replicates of five broiler chicks each in a completely randomized design. T1 was given commercial diet without mushroom while T2, T3, and T4 were given same commercial feed supplemented with dried mushroom at 1%, 1.5% and 2% from day old to 28 days of age. At this point, blood was collected by the use of syringe and needle through their wing vein for use in assaying the blood. Data collected were analyzed using one-way Analysis of variance. There was improvement on some blood parameters. PCV was highest at 1% inclusion (30.30 ± 0.53%) as against 23.50 ± 0.64% in the control while HB declined progressively from 8.53 ± 0.023 g/dl (control) to 7.23 ± 0.035 g/dl (2% inclusion). RBC count decreased from 2.85 ± 0.031 ×10⁶/μL in the control to 2.24 ± 0.023 ×10⁶/μL in the 1.5% group. Notwithstanding, PCV fall within the normal range for broilers (25.60-32.50% for PCV, 8.93 - 10.45g/dl for HB and 3.53-3.80 x 106/μL for RBC). Cholesterol reduced from 142.4 ± 0.69 mg/dl in the control to 127.6 ± 1.36 mg/dl at 2% inclusion, while triglyceride declined from 102.3 ± 0.31 mg/dl to 60.6 ± 1.08 mg/dl. In contrast, high-density lipoprotein (HDL) increased progressively from 89.1 ± 1.37 mg/dl (control) to 109.4 ± 0.47 mg/dl (2%). Also, there was a significant improvements in liver markers, reduced low-density lipoprotein (LDL) coupled with increased high-density lipoprotein (HDL).